Learning styles preferences using fuzzy logic system / Wan Nurshazelin Wan Shahidan, Nur Rusmawati Ishak and Siti Nor Nadrah Muhamad - Wan Shahidan, Wan Nurshazelin; Ishak, Nur Rusmawati; Muhamad, Siti Nor Nadrah (UiTM Cawangan Perlis, 2021)
Every individual has their own natural or habitual pattern of gathering and processing information in learning situations. The different environment between school and university studies will pose a significant impact on the learning style of students. The objectives of this study are to analyse the most preferred learning style among first-year diploma students in Universiti Teknologi MARA (UiTM) Perlis Branch and compare the preferred learning style among male and female students using the Fuzzy Logic System. There were nine variable inputs in determining the fuzzy logic learning styles which are reading likeness, by nature, thinking time, speaking rate, activity level, activity enjoyment, visual distraction, auditory distraction and using instruction to obtain the VARK (visual, auditory, read/write, kinaesthetic) learning styles output. The results showed that 32% of the students prefers visual learning styles based on the VARK questionnaire while for the fuzzy inferences system, 40% of the students prefer visual learning style. Additionally, 45% of male students preferred visual learning styles followed by reading/writing and kinaesthetic learning styles of 20%. Among female students, 34% of them also showed preferred visual learning styles, followed by reading/writing learning styles. It is concluded that the vast majority of UiTM Perlis Branch students prefers visual learning styles in their studies.